Re: The Effect of Pelvic Organ Prolapse Repair on Vaginal Sensation - Lowenstein L; Gartman I; Gruenwald I (Journal of Urological Surgery)
The association between the pelvic organ prolapse (POP) and sensory functioning of the genital region has not been studied well. It is not also obvious whether the changes occurring at the same time are the cause or the result. In this study, the authors investigated the quantitative sensory changes one day before and 6 months after the surgical repair of POP by robotic sacrocolpopexy. They also used the Pelvic Organ Prolapse Distress Inventory-6 which quantifies the bother and distress caused by the pelvic symptoms. By this method, the initial perception of a sensation of temperature (hot or cold) and vibration was measured. After six months, sensitivity to thermal stimuli was found to be significantly improved, but there was no significant change in the vaginal and clitoral vibratory sensory thresholds. The value of reduced sensation in the genitals is not a well-known issue. We know that the thermal and vibratory sensations are diminished in female sexual dysfunction and they can be important in orgasmic function also. It is a well-designed study although it has some limitations. The anatomic correction in POP surgery could improve the genital sensation. Prevention or, at least, early correction of POP can provide serious advantages not only for urinary system but also for the genital functions of women.